Relationship between Knowledge of Menstruation with the Female Teenage Readiness in Facing Menarche - Rohmah, Elis; Djamahar, Refirman; Rahayu, Sri (Universitas Negeri Jakarta, 2015)
Adolescence is a critical period in a human development stage. One of the most important periods for female teenage is menarche that causes different impact, one of them is psychological impact. Acquired knowledge about menstruation will affect the perception of adolescents about menarche that can also affect the readiness of the girls in facing menarche. The purpose of this study was to determine the relationship between knowledge about menstruation with the readiness of female teenage in facing menarche. This research was conducted in SDN lubang buaya 01 and 05 on May-June 2015. Data obtained by giving knowledge and readiness questionnaire to 47 respondents in SDN Lubang Buaya 01 and as many as 51 respondents in SDN Lubang Buaya 05. Data were analyzed by using a simple correlation - regression test. The correlation coefficient (rxy) was 0.593 indicates that there is a moderate possitive relationship between Knowledge of Menstruation with the Female Teenage Readiness in Facing Menarche through the regression model Å¶ = 29.831 + 0,649X. It can be conclude that the knowledge has a moderate positive relationship with the female teenage readiness in facing menarche.